PP.30.15: INDIVIDUAL AND COMBINED IMPACT OF MODIFIABLE RISK FACTORS ON HYPERTENSION INCIDENCE FROM THE KOREAN COMMUNITY-BASED COHORT. (June 2015) - Park, H.; Lim, N.; Ahn, Y.; Cho, M.
Abstract : Objective: The individual and combined impact of modifiable lifestyle factors on hypertension was evaluated in the Korean middle-aged population. Design and method: 2, 379 men and 2, 622 women aged 40 to 69, without hypertension and cardiovascular diseases at baseline, were followed during 4 years. Modifiable risk factors were consisted of five high-risk lifestyle factors (being obesity, heavy alcohol intake or alcohol abstinence, high sodium intake, lack of exercise, and ever cigarette smoking). Cox proportional hazard regression was used to estimate the hazard ratios for the individual and combined risk factors. To assess the individual and combined impact of lifestyle risk factors for hypertension incidence, population attributable risk (PAR) was calculated. Results: Individuals with lower education and monthly income level had increasing number of high-risk lifestyle factors. The PAR were 21% for being obesity, 22% for lack of exercise, 18% of abstinent or heavy drinking, 9% for ever cigarette smoking, and 8% for high sodium intake. All individual lifestyle risk factors were positively associated with the incidence of hypertension, except for ever cigarette smoking (Table). Hypertension incidence was increased by increasing number of high-risk lifestyle factors (Figure). Men and women who had 4 or 5 high-risk lifestyle factors were a 1.79-fold (95% CI, 1.15–2.79) and a 2.38-fold (95% CI, 1.70–3.34) more likely to develop hypertension during 4 years than those who have none or one risk factor, respectively. The cumulative incidence in individuals with four or five high-risk lifestyle factors was higher in women than in men (24.4% in men vs 33.7% in women). Figure. No caption available. Conclusions: Four modifiable lifestyle risk factors, obesity, lack of exercise, none or heavy drinking, and high sodium intake, were significantly associated with hypertension incidence. The PAR for combination of five risk factors was about 58% for hypertension. Especially, our data showed that a regular exercise and a weight loss program will play a key role in decreasing a burden caused by hypertension and its complications.